Sentiment-augmented supply and demand equations for the dry bulk shipping market - Nektarios Michail; Konstantinos D. Melas (Economies, 2021)
We present, for the first time in the literature, empirical estimates of the supply and demand curves for the ocean-going dry bulk sector, using a three-stage least squares methodology. Furthermore, we augment these functions with sentiment, which appears to have a positive and significant impact on supply. This supports the view that the outlook that shipowners have about the market will undoubtedly influence their decisions regarding purchasing vessels or bringing them out of lay up. Thus, our results highlight the fact that future expectations have an impact on current pricing, albeit indirectly, through their impact on the supply side. Our results further enhance the behavioral economics literature and provide important insights for both academics and professionals.
Keywords: 330; demand; dry bulk; sentiment; shipping markets; supply; three-stage least squares